The Potential of Acacia angustissima Leaf Meal as a Supplementary Feed Source in Broiler Finisher Diets - Ncube , S.; Hamudikuwanda, H.; Banda, P. (International Journal of Poultry Science, 2011)
This study evaluated, in a completely randomized design with five replicates, performance of Ross broiler chicks fed diets with 0 to 15% of Acacia angustissima leaf meal (leaf meal) from the fifth week to the end of the eight week of growth. Feed intake, weekly bodyweight, bodyweight gain, feed conversion ratio and carcass characteristics were determined. Feed intake, body weight gain and feed conversion ratio in birds on the 0% to 5% were not different (p<0.05). Broilers on 10% and 15% leaf meal had lower (p<0.05) bodyweight gain than those on the 0% and 5% leaf meal. However, birds on the 10% and 15% leaf consistently gained bodyweight and did not show any abnormalities or signs of disease. It is concluded that up to 15% leaf meal can be included in broiler finisher diets; however, 5% leaf meal appears to be the optimum inclusion rate for normal growth.